2016
DOI: 10.1109/tnsre.2015.2492860
|View full text |Cite
|
Sign up to set email alerts
|

User Evaluation of a Dynamic Arm Orthosis for People With Neuromuscular Disorders

Abstract: This paper presents the results of an online survey conducted with users of a functional upper extremity orthosis called the Wilmington Robotic EXoskeleton (WREX). The WREX is a passive anti-gravity arm orthosis that allows people with neuromuscular disabilities to move their arms in three dimensions. The paper also describes the design of a novel lightweight 3-D printed WREX used for ambulatory children. Three different versions of the WREX are now offered to patients. Two can be mounted on a wheelchair and o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
46
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
4
2
1

Relationship

1
6

Authors

Journals

citations
Cited by 28 publications
(46 citation statements)
references
References 14 publications
0
46
0
Order By: Relevance
“…In this study, the children and their A concurrent study using an online questionnaire to rate the performance of 10 common activities of daily living while wearing the WREX and while not wearing the WREX was conducted (Gunn, Shank, Eppes, Hossain, & Rahman, 2015). Fifty-five participants completed the online survey.…”
Section: Literature Reviewmentioning
confidence: 99%
“…In this study, the children and their A concurrent study using an online questionnaire to rate the performance of 10 common activities of daily living while wearing the WREX and while not wearing the WREX was conducted (Gunn, Shank, Eppes, Hossain, & Rahman, 2015). Fifty-five participants completed the online survey.…”
Section: Literature Reviewmentioning
confidence: 99%
“…The WREX (JAECO Orthopedic, USA) [34] and the TOP (Focal Meditech, the Netherlands) are passive arm supports that have been in the market for more than 20 years. The WREX (JAECO Orthopedics, USA) is now available in two versions: a metal version that attaches to the wheelchair or to a table, and a wearable version, known as Baby WREX, that combines 3D printed plastic parts and metal parts for ambulatory children [35]. More recent commercially available passive arm supports include the Sling, the Dowing and the Balancer (Focal Meditech, the Netherlands), the VERTICAL M.A.G.…”
Section: Classification Of Arm Supportsmentioning
confidence: 99%
“…Users also reported more improvement of arm function with the wheelchair-mounted WREX than with the body-mounted version. Aesthetics, fitting, and reimbursement were identified as areas for improvement [35]. Finally, a user evaluation study with the Neater arm support concluded that the use of the Neater arm support by adults and teenagers with neuromuscular disorders could greatly improve their independence, confidence, and ability to engage in social situations [38].…”
Section: Effectiveness Of Arm Supportsmentioning
confidence: 99%
See 2 more Smart Citations